2014
DOI: 10.1007/s10964-014-0148-1
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Vulnerability–Stress Model with Brooding and Reflection to Explain Depressive Symptoms in Adolescence

Abstract: To date, few studies have attempted to test the effect of rumination and its components (brooding and reflection) on depression from a diathesis-stress approach, which involves an interaction between stressors and rumination. The purpose of this study was to assess whether rumination moderates the predictive association between stress and depressive symptoms in adolescents. The possible moderation effect of gender on the relationships between the two rumination components and depressive symptoms over time was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…This was further evidenced by the lack of a significant correlation between the RRS Reflection subscale and depression levels in the present sample. Our results add to the mixed evidence for identifying the predictive relationships between self-reflection and depression-related outcomes (see Arditte and Joormann, 2011; Johnson and Whisman, 2013: Padilla Paredes and Calvete Zumalde, 2015; Johnson et al, 2016; Artiran et al, 2019).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This was further evidenced by the lack of a significant correlation between the RRS Reflection subscale and depression levels in the present sample. Our results add to the mixed evidence for identifying the predictive relationships between self-reflection and depression-related outcomes (see Arditte and Joormann, 2011; Johnson and Whisman, 2013: Padilla Paredes and Calvete Zumalde, 2015; Johnson et al, 2016; Artiran et al, 2019).…”
Section: Discussionsupporting
confidence: 61%
“…Conversely, self-reflection – or the purposeful and non-judgmental appraisal of the positive or neutral content of distressing events – is believed to be an adaptive form of self-focused attention that facilitates problem solving (Treynor et al, 2003; Kross et al, 2005) and supports emotional well-being (Brans et al, 2013). Notably, the relationship between self-reflection and depression is less clear than that for brooding, with some studies finding no association between reflection and depression outcomes (Koval et al, 2012; Jose and Weir, 2013; Moore et al, 2013; Johnson et al, 2016; Tsypes and Gibb, 2016; Junkins and Haeffel, 2017; Artiran et al, 2019), others showing no distinction between its effects and those of brooding (Johnson and Whisman, 2013; Wilkinson et al, 2013; Padilla Paredes and Calvete Zumalde, 2015), and yet others observing the positive benefits of reflection on depression-relevant processes (Joormann et al, 2006; Burwell and Shirk, 2007; Arditte and Joormann, 2011). Thus, while brooding and reflection are forms of self-focused attention, the two differ as to the target of salient focus and perhaps relate to divergent affective outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Increased brooding rumination in children was associated with a mother's past depression status and thus may be linked with a specific genetic heritability factor (Gibb, Grassia, Stone, Uhrlass, & McGeary, 2012;Woody et al, 2016). In adolescents, brooding rumination is predictive of future depressive episodes, especially in girls (Burwell & Shirk, 2007;Cox, Funasaki, Smith, & Mezulis, 2011;Padilla Paredes & Calvete Zumalde, 2015). Also, levels of brooding rumination mediate the relationship between childhood trauma and depressive symptoms (Raes & Hermans, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…When the concept of rumination – defined as a specific response style that increases the incidence, severity and duration of depressive states – was formulated (Nolen-Hoeksema, 1991), ruminative tendency began to be considered as an important factor that increases the risk of depression (see Thomsen, 2006, for a review) and a predictor of depressive symptoms in non-clinical populations (e.g., Nolen-Hoeksema et al, 2007). The results of recent studies have suggested that rumination may interact with stress and thus increase depression symptoms (Skitch and Abela, 2008; Abela and Hankin, 2011; Bastin et al, 2015; Hamlat et al, 2015; Padilla Paredes and Calvete Zumalde, 2015; Connolly and Alloy, 2017; Shapero et al, 2017).…”
Section: Introductionmentioning
confidence: 99%